2010
DOI: 10.1007/dcr.0b013e3181ca7dc2
|View full text |Cite
|
Sign up to set email alerts
|

Six Years of Experience With Sacral Nerve Stimulation for Fecal Incontinence

Abstract: Sacral nerve stimulation is a simple, safe, and minimally invasive technique with low morbidity and excellent results, which appear to be maintained for the first 6 years after the procedure. For patients who underwent the treatment, median Wexner incontinence score decreased significantly after a median follow-up of 24 (range, 3-72) months. Twelve percent were explanted. The infection rate was 1.6%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 40 publications
8
44
1
3
Order By: Relevance
“…This is a procedure that in the reviewed literature has a low complication or adverse effects rate, including surgical site infection. The incidence of infection in our series was 4%, a value similar to that described in other studies (range 1.6-10.8%) (13,14). In both cases infection occurred after definitive pacemaker implantation and prompted its withdrawal.…”
Section: Discussionsupporting
confidence: 89%
“…This is a procedure that in the reviewed literature has a low complication or adverse effects rate, including surgical site infection. The incidence of infection in our series was 4%, a value similar to that described in other studies (range 1.6-10.8%) (13,14). In both cases infection occurred after definitive pacemaker implantation and prompted its withdrawal.…”
Section: Discussionsupporting
confidence: 89%
“…Our study supports the findings of Brouwer and Duthie who demonstrated no correlation between pudendal nerve latency testing and outcomes following SNM [26]. Studies looking at the mechanism of action of SNM have shown that in addition to improvement in muscle function, SNM also modulates sacral reflexes that regulate rectal sensitivity and contractility, anal motility and brain activity relevant to the continence mechanism [27][28][29]. It may be possible that current testing modalities are simply not able to detect which of the stages in these complex interactions are predictive of success with SNM.…”
Section: Discussionsupporting
confidence: 89%
“…The PNE test is conducted over a period of 2-3 weeks. A positive test response is achieved for 70 %-90 % of patients (19)(20)(21)(22). In those who have an implanted stimulator, the effect is sustained in 70 %-90 % after 2-5 years (19,22,23).…”
Section: Anal Incontinencementioning
confidence: 99%